PEMBERDAYAAN MASYARAKAT PALIMO INDAH KOTA PADANG MELALUI KEGIATAN PENGHIJAUAN LINGKUNGAN DI DAERAH PERKOTAAN - Nugraha Ramadhan; Auzar Syarif; Roza Yunita; Fitri Ekawati; Winda Purnama Sari; Aprizal Zainal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Reforestation is an effort to restore, maintain and improve the condition of the land so that it can be used optimally according to its original function. Several steps to realize the reforestation of the residential environment in a narrow area include utilizing the existing land, choosing suitable plants, and providing utmost care. This activity aimed to increase public understanding and knowledge regarding narrow land for reforestation in urban areas. The method used was a direct approach, namely, conducting interviews with the community and holding outreach and direct demonstrations in the field. The result of this empowerment activity was that the communities, especially the residents of Palimo Indah, are very enthusiastic about participating in the greening of the environment. The selected plants consider their multifunctionality for the environment's good, such as the absorption of air pollution and family medicinal plants. The three tree seedlings are useful for reforestation and have economic value, namely the Sungkai plant, Petai tree, and Agarwood sap-producing plant. Planting has been carried out at several location points by collaboration as a form of community empowerment, namely on the park's outskirts and on the riverbanks in the Palimo Indah, Pauh District, Padang.